Science Alone Won’t Do It! South Africa’s Endangered Humpback Dolphins Sousa plumbea Face Complex Conservation Challenges - Plön, Stephanie; Atkins, Shanan; Cockcroft, Vic; Conry, Danielle; Dines, Sasha; Elwen, Simon; Gennari, Enrico; Gopal, Keshni; Gridley, Tess; Hörbst, Sandra; James, Bridget S.; Penry, Gwenith; et al. (Frontiers in Marine Science, 2021)
The SouSA Consortium is a formalised network of scientists and conservationists established in 2016 to combine knowledge and research efforts, and make coordinated decisions with the aim of conserving the endangered Indian Ocean humpback dolphin (Sousa plumbea) in South African waters. The first collaborative project collated available photo-identification data in an attempt to refine a national population estimate and investigate movements between research sites. This work indicated that there were less than 250 uniquely identified animals, with the population divided into two communities: one on South Africa’s south-coast (Agulhas bioregion) and another on the east-coast (Natal bioregion). Environmental factors almost certainly play a role in the declining numbers of the species in South African waters. However, individual threats and solutions are challenging to identify as the South African marine environment is undergoing significant natural and anthropogenic changes with major shifts in the distribution and numbers of some prey, competitor and predator species. Therefore, we believe that a continued investigation of potential contributing factors, and their interaction, will take too long, inevitably resulting in another case of “documenting extinction”. With this in mind, we present the results of a SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis in an effort to help us identify the next steps to take towards the conservation of humpback dolphins in South African waters. Unanimously, the Consortium members conclude that no single cause for the rapid decline of humpback dolphins in South African waters can be identified, and that the cumulative effects of multiple stressors, which are difficult to pinpoint and mitigate, are impacting population numbers. While highlighting the need for continued research, the Consortium suggests a shift towards more action-focused conservation efforts.